Mycoplasma pneumoniae lipids license TLR‐4 for activation of NLRP3 inflammasome and autophagy to evoke a proinflammatory response. (29th September 2020) - Luo, H.; He, J.; Qin, L.; Chen, Y.; Chen, L.; Li, R.; Zeng, Y.; Zhu, C.; You, X.; Wu, Y.
Summary: Mycoplasma pneumoniae is an obligate pathogen that causes pneumonia, tracheobronchitis, pharyngitis and asthma in humans. It is well recognized that membrane lipoproteins are immunostimulants exerting as lipopolysaccharides (LPS) and play a crucial role in the pathogenesis of inflammatory responses upon M. pneumoniae infection. Here, we report that the M. pneumoniae ‐derived lipids are another proinflammatory agents. Using an antibody‐neutralizing assay, RNA interference or specific inhibitors, we found that Toll‐like receptor 4 (TLR‐4) is essential for M. pneumoniae lipid‐induced tumour necrosis factor (TNF)‐α and interleukin (IL)‐1β production. We also demonstrate that NLR family pyrin domain containing 3 inflammasome (NLRP3) inflammasome, autophagy and nuclear factor kappa B (NF‐κB)‐dependent pathways are critical for the secretion of proinflammatory cytokines, while inhibition of TLR‐4 significantly abrogates these events. Further characterization revealed that autophagy‐mediated inflammatory responses involved the activation of NF‐κB. In addition, the activation of NF‐κB promoted lipid‐induced autophagosome formation, as revealed by assays using pharmacological inhibitors, 3‐methyladenine (3‐MA) and Bay 11‐7082, or silencing of atg5 and beclin‐1 . These findings suggest that, unlike the response to lipoprotein stimulation, the inflammation in response to M. pneumoniae lipids is mediated by the TLR‐4 pathway, which subsequently initiates the activation of NLRP3 inflammasome and formation of a positive feedback loop between autophagy and NF‐κB signalling cascade, ultimately promoting TNF‐α and Il‐1β production in macrophages. Abstract : TLR4 is usually not assumed to be involved in Mycoplasma recognition. In this study we showed that the Mycoplasma pneumoniae ‐derived lipids did interact with TLR4 which subsequently initiates the activation of NLRP3 inflammasome and formation of a positive feedback loop between autophagy and NF‐κB signalling cascade, ultimately promoting proinflammatory cytokines production in macrophages.